TNXB Mutations Can Cause Vesicoureteral Reflux - Gbadegesin, Rasheed A. (American Society of Nephrology, 2013)
Primary vesicoureteral reflux (VUR) is the most common congenital anomaly of the kidney and the urinary tract, and it is a major risk factor for pyelonephritic scarring and CKD in children. Although twin studies support the heritability of VUR, specific genetic causes remain elusive. We performed a sequential genome-wide linkage study and whole-exome sequencing in a family with hereditary VUR. We obtained a significant multipoint parametric logarithm of odds score of 3.3 on chromosome 6p, and whole-exome sequencing identified a deleterious heterozygous mutation (T3257I) in the gene encoding tenascin XB (TNXB in 6p21.3). This mutation segregated with disease in the affected family as well as with a pathogenic G1331R change in another family. Fibroblast cell lines carrying the T3257I mutation exhibited a reduction in both cell motility and phosphorylated focal adhesion kinase expression, suggesting a defect in the focal adhesions that link the cell cytoplasm to the extracellular matrix. Immunohistochemical studies revealed that the human uroepithelial lining of the ureterovesical junction expresses TNXB, suggesting that TNXB may be important for generating tensile forces that close the ureterovesical junction during voiding. Taken together, these results suggest that mutations in TNXB can cause hereditary VUR.